Pengaruh Perputaran Kas, Modal Kerja dan Perputaran Piutang terhadap Likuiditas (Current Ratio) pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017 - Henny Indriani Susantri Manullang; Enda Noviyanti Simorangkir; Desy Octavia; Dessy Kristy Parapat; Winarti Halawa; Maritta Hirawati (Politeknik Negeri Lampung, 2019)
This study aims to examine the effect of cash turnover, working capital and accounts receivable turnover towards liquidity (current ratio) in consumer goods companies listed on the Indonesia Stock Exchange (IDX) for the 2014-2017 period both simultaneously and partially and to find out which variables are free, and which has a significant effect on liquidity in consumer goods companies listed on the Indonesia Stock Exchange. The population in this study - 24 Consumer Goods companies - was defined through purposive sampling method in the Consumer Goods companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2017 period as well as predetermined criteria. The research applied analytical method of multiple linear regression analysis with SPSS 22 tools. The results of the hypothesis testing of the T-test show that cash turnover variables have an effect on significant liquidity while working capital and receivable turnover variables do not affect the liquidity in Consumer Goods companies in Indonesia stock exchange.Keywords : cash turnover, working capital, accounts receivable turnover, liquidity, current ratio